Dimeric packing of molecular clips induced by interactions between π-systems1. Issue 12 (28th March 2015) - Wang, Jungang; Wang, Miao; Xiang, Jiachen; Cao, Liping; Wu, Anxin; Isaacs, Lyle
<x xml:space="preserve">Abstract</x> We report the first observation synthesis and X-ray structures of seven glycoluril clips that feature extended aromatic sidewalls; compounds 1 and 2 are the first examples of the out–out dimeric motif.